LEGALITAS ULTRA PETITA DALAM HUKUM ACARA PIDANA PADA PUTUSAN PENGADILAN” - Luis Luis (Fakultas Hukum Universitas Tarumanagara, 2021)
Based on Law no. 8 of 1981 concerning the Criminal Procedure Code Article 182 paragraph (4) states that: